2007
DOI: 10.1159/000113015
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Familial Gastric Cancer in Tuscany, a Region in Italy

Abstract: Objectives: Only 1% of diffuse gastric cancers occur in families with autosomal dominant gastric cancer susceptibility. Germline mutations in the E-cadherin gene account for the hereditary diffuse gastric cancer (HDGC) syndrome. We studied a large cohort of gastric cancer patients from Tuscany, a region in Italy, to evaluate the presence of familial clustering of gastric cancer. Methods: 238 pedigrees were retrospectively studied by structured interviews. All probands with diagnosed gastric cancer were contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
0
21
1
Order By: Relevance
“…20 It is well known that the prevalence of H. pylori infection in the general population is higher in countries with a higher incidence of gastric cancer 21 ; in Tuscany, the incidence of gastric cancer is very high compared with other regions of Italy. 22 Epidemiologic factors and the sensitivity of the methods used could explain the high rates of H. pylori positivity reported in the current series.…”
Section: Discussionmentioning
confidence: 75%
“…20 It is well known that the prevalence of H. pylori infection in the general population is higher in countries with a higher incidence of gastric cancer 21 ; in Tuscany, the incidence of gastric cancer is very high compared with other regions of Italy. 22 Epidemiologic factors and the sensitivity of the methods used could explain the high rates of H. pylori positivity reported in the current series.…”
Section: Discussionmentioning
confidence: 75%
“…Japanese studies [4,7] reported that the undifferentiated histological type was dominant in FGC, and there was a predisposition to the intestinal type when both parents suffered from GCs while to the diffuse type when both parents suffered from non-GCs. The dominance of the intestinal type and the diffuse type was reported in Italy and Poland, respectively [13,16,20] . These variations indicate that familial predisposition to GC may be a multifactor disease.…”
Section: Discussionmentioning
confidence: 94%
“…However, the frequency of non-GC in family members differed from the results in other reports. For example, colorectal, lung, and uterine cancers were the highest in ranking in a Japanese report [9] , while colorectal, breast, and lung cancer were prevalent in an Italian report [20] , lung/larynx cancer, gastrointestinal cancer, and leukemia/lymphoma were most frequent in a study from Turkey [18] , and colorectal and lung cancer were most common in a report from Taiwan [6] . In general, the overall ranking of associated non-GCs in family histories of GC varied from region to region, but the preceding tumors were usually the most frequent ones occurring in that general population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, in Tuscany there are some areas, such as the Mugello in the Florence district, with high GC incidence and mortality rates in comparison to the national rates, where previous epidemiological studies have identified many familial groups with a high rate of GC among first-degree relatives [4]. A recent study has also shown a high prevalence of familial hereditary diffuse GC in Tuscany [5]. …”
Section: Introductionmentioning
confidence: 99%